Liraglutide attenuates autoimmune myocarditis by inhibiting NLRP3 and NF-κb pathways - Lijuan Zhang; Lishuai Han; Yang Lu; Quanzhou Chen (Scientific Reports)
Abstract Myocarditis, an inflammatory heart disease, often leads to severe cardiac dysfunction, including dilated cardiomyopathy and sudden death. Current treatments for myocarditis remain limited, necessitating the exploration of new therapeutic approaches. Liraglutide, a glucagon-like peptide-1 receptor agonist widely used for type 2 diabetes and obesity, has shown anti-inflammatory effects in other cardiovascular diseases. In this study, we investigated liraglutide’s effects on autoimmune myocarditis. Our findings demonstrated that liraglutide significantly reduced myocarditis severity by lowering heart weight/body weight ratio, serum cardiac troponin T levels, cardiac fibrosis, and inflammatory infiltration. Echocardiography showed improved left ventricular function, while immunofluorescence and RT-qPCR analyses revealed decreased T-cell and macrophage infiltration and reduced expression of pro-inflammatory cytokines. RNA sequencing indicated that liraglutide modulates the NLRP3 inflammasome and NF-κB pathways. These results suggest that liraglutide has the potential to be a therapeutic agent for myocarditis.